2016
DOI: 10.5603/kp.a2016.0063
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in cardiovascular disease

Abstract: Associate Professor Krzysztof Małyszczak is a head of the Division of Psychotherapy and Psychosomatic Medicine at the Department of Psychiatry, Wroclaw Medical University. He is a psychiatrist and a psychotherapy supervisor, the organiser and chief specialist in a ward for the treatment of neuroses and personality disorders. His projects are focused on mood, anxiety, and personality disorders, especially in cases coexistence of somatic diseases. He participated in a study of factors affecting depression in can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…However, considering the overlap of clinical manifestations, screening instruments, and pharmacological treatments for anxiety and depression, it would be important to manage emotional disorders in patients with acute coronary events in clinical practice. [38][39][40][41] Some implications could be summarised for clinical practice and future research in this field. The potential pathophysiological basis for the association between anxiety and poor prognosis in patients with ACS may include the following: anxiety is a stressor that might further burden cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the overlap of clinical manifestations, screening instruments, and pharmacological treatments for anxiety and depression, it would be important to manage emotional disorders in patients with acute coronary events in clinical practice. [38][39][40][41] Some implications could be summarised for clinical practice and future research in this field. The potential pathophysiological basis for the association between anxiety and poor prognosis in patients with ACS may include the following: anxiety is a stressor that might further burden cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…These statistical observations are an important argument supporting the significance of drawing attention to the problem of comorbidity, or co-occurrence of anxiety disorders and cardiovascular diseases. The presence of anxiety disorders makes it more difficult for patients to adapt to a troublesome situation caused by a chronic disease, and is related to lower quality of life, more difficulties in understanding and following medical recommendations, and slower recovery after acute cardiovascular events [76,77,78].…”
Section: The Use Of Beta Blockers In Treating Anxiety Disordersmentioning
confidence: 99%
“…Obecność zaburzeń lękowych utrudnia pacjentom ich adaptację do trudnej sytuacji spowodowanej przewlekłą chorobą i wiąże się z niższą jakością życia, większą trudnością w absorbowaniu i stosowaniu się do zaleceń lekarskich, oraz wolniejszym powrotem do zdrowia po ostrych epizodach sercowo -naczyniowych [76,77,78]. Lęk jest czynnikiem ryzyka rozwoju chorób sercowo -naczyniowych, ale także wystąpienia powikłań zawału serca (arytmie lub kolejne epizody zawału serca) i jest również związany z większą śmiertelnością w tej grupie pacjentów [77].…”
Section: Zastosowanie Beta-adrenolityków W Leczeniu Zaburzeń Lękowychunclassified
“…Several studies have indicated an association between anxiety and cardiovascular risk factors and CAD [9]. Anxiety seems to be an adequate predictor of CAD in conjunction with depression [10].…”
Section: Discussionmentioning
confidence: 99%